Comparison of Clinical Codes with Standards of Genitourinary Disease in Public Hospital of Sidoarjo - Vina Fauzia; Umi Khoirun Nisak; Cholifah Cholifah (IKIP Mataram, 2023)
The accuracy of data diagnosis is important for clinical data management, reimbursement, and issues related to healthcare and services. Based on preliminary observations, it was found that the inaccuracy of the diagnosis code maker with the genitourinary disease standard at the Sidarjo District Hospital. The purpose of this study was to find out the comparison of coder clinical codes with genitourinary disease standards at the sidoarjo district hospital. The method used was quantitative with random sampling techniques presented in the form of frequency tables and cross tabulations and tested using the chi-square test. This study used medical records for inpatient genitourinary cases in 2022, with a total sample of 80 medical records. The results showed that completeness, timeliness, and accuracy had a significant influence on coding accuracy. Completness ( completeness of supporting information) obtained 58,8% complete medical record documents and 51.3% incomplete medical record documents (p=0.012). Accuracy (coding accuracy):52.5% of medical record documents were accurate and 47.5% of medical record documents were inaccurate (p=0,0001). This study suggests improving the quality of coding by conducting coding training and evaluating coding audits to support coding speed.